Tingkat Kepuasan Konsumen Terhadap Kualitas Pelayanan Minimarket - Sufiyanti, Ety; Sayutu, A. Jalaludin; Windarti, Ayu Oka (Jurnal Riset Bisnis dan Investasi, 2017)
This study determine the level of customer satisfaction towards service quality at Minimarket Mutiara Indah Palembang, with purpose to determine how percentage level of customer satisfaction, and also to determine what kind of service quality dimension which had dominant. Collected data had used quesioner with the respondent 60 people, and the technique of collected sample used Non Probability Sampling with Accidental Sampling method. Based on the result known that average percentage from every dimension were tangible dimension was 65,1 %, reability dimension was 74%, responsiveness dimension was 79,8 %, assurance dimension was 74,2 % and empathy dimension was 75,6%. So, dimension which has dominant at Minimarket Mutiara Indah Palembang was responsiveness dimension with 79,8% to the fast of employee to find product which customer want to bought.